Setting the Relationship between Human-Centered Approaches and Users’ Digital Well-being: A Review - Polanco-Diges, Leticia; Ramón Saura, José; Pinto, Patricia (Journal of Tourism, Sustainability and Well-being, 2022)
With the advancement of technology and advent of the new digital era, the society is getting increasingly exposed to novel technologies, digital platforms, or smart devices. This reality opens a wide range of questions about the benefits and challenges of technology and its impact on humans. In this context, the present study investigates the relationship between human-centered approaches and their application to achieve users’ digital well-being, as well as explores whether marketing and business industry are sufficiently considering human-centered approaches in their implementation of practices that care for users’ digital wellbeing. To this end, we conduct a systematic literature review. The exploratory results confirm that the implementation of human-centered approaches makes it possible to achieve a greater user well-being in the marketing and management sector. Additionally, we also identify and discuss seven more relevant areas. Our review concludes with a discussion of the theoretical and practical implications of our findings for further research on the use of human-centric and digital well-being concepts.